2017
DOI: 10.1016/j.advwatres.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the release of Escherichia coli from soil into overland flow under raindrop impact

Abstract: a b s t r a c tPathogen transport through the environment is complicated, involving a variety of physical, chemical, and biological processes. This study considered the transfer of microorganisms from soil into overland flow under rain-splash conditions. Although microorganisms are colloidal particles, they are commonly quantified as colony-forming units (CFUs) per volume rather than as a mass or number of particles per volume, which poses a modeling challenge. However, for very small particles that essentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…As has been documented previously, E. coli concentrations were highly correlated with sediment concentrations and related variables, including total P (Gentry et al, 2006;Vidon et al, 2008). According to previous findings (Wang, 2015;Wang et al, 2017;Wang et al, 2018), one reason was that transport of E. coli and sediment can be explained by the same mechanisms, especially when stormwater dominates. The high correlation between the increase of E. coli level and the occurrence of storm and the increase of sediments (Table 5) was generally explained by surface erosion and the co-transport of E. coli both alone and bound to eroding sediments (Muirhead et al, 2006a;Oliver et al, 2005).…”
Section: Pc1mentioning
confidence: 92%
See 1 more Smart Citation
“…As has been documented previously, E. coli concentrations were highly correlated with sediment concentrations and related variables, including total P (Gentry et al, 2006;Vidon et al, 2008). According to previous findings (Wang, 2015;Wang et al, 2017;Wang et al, 2018), one reason was that transport of E. coli and sediment can be explained by the same mechanisms, especially when stormwater dominates. The high correlation between the increase of E. coli level and the occurrence of storm and the increase of sediments (Table 5) was generally explained by surface erosion and the co-transport of E. coli both alone and bound to eroding sediments (Muirhead et al, 2006a;Oliver et al, 2005).…”
Section: Pc1mentioning
confidence: 92%
“…As E. coli was found to be eroded from the top soil (Wang, 2015;Wang et al, 2017;Wang et al, 2018) and resuspended from the bottom of the stream together with sediments (Ferguson et al, 2003;Jamieson et al, 2005), it was expected that E. coli concentrations were significantly positively correlated with PC1. As has been documented previously, E. coli concentrations were highly correlated with sediment concentrations and related variables, including total P (Gentry et al, 2006;Vidon et al, 2008).…”
Section: Pc1mentioning
confidence: 99%
“…The well‐known Hairsine–Rose model (Hairsine & Rose, ) assumed that small particle transfer from soil into overland run‐off through a shield layer. Wang et al () confirmed that the Gao model (Gao et al, , ) is identical to the Hairsine–Rose model (Hairsine & Rose, ) for simulating the transport of colloidal from soil into overland storm flows. Through these studies, researchers have gained a generally good understanding of the solute transport from soil into overland flow.…”
Section: Introductionmentioning
confidence: 88%
“…Muirhead et al (2006) looked at the interaction between E. coli and soil particles in overland flow across saturated soil and found that E. coli were mainly attached to mineral particles smaller than 2 µm and, once mobilized, E. coli remained in suspension. Using lab experiments, Wang et al (2017) studied mineral colloid and bacteria co-release from soil into overland flow under raindrop impact (splash erosion). They found that the temporal patterns of release of mineral colloid and bacteria were identical (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using lab experiments, Wang et al (2017) studied mineral colloid and bacteria co-release from soil into overland flow under raindrop impact (splash erosion). They found that the temporal patterns of release of mineral colloid and bacteria were identical (Wang et al, 2017). But they were unable to specifically identify the role of clay in the E. coli release process (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%